Consumer Willingness to Pay for Preservative-Free Food: The Case of Beijing - Xiaohua Yu; Yinchu Zeng; Yuanyuan Liu (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
Consumers are facing a trade-off between the benefits of an increase in the length of the shelf life of food, such as low food costs, and the potential health damages caused by food preservatives. However, few studies in the current literature place emphasis on food preservatives, neither from a scientific perspective nor from an economic perspective. This causes a lot of controversies about government regulations. By constructing a theoretical framework and using a survey of 293 customers from 25 supermarkets in Beijing, this paper studies the consumer attitude towards food preservatives and attempts to fill the gap in the current literature. The main findings include that food price, and consumers' age and income are important for the willingness to pay (WTP) for 'preservative-free food' in Beijing. In particular, food price and consumer incomes are positively correlated with the WTP and there might be an inverted U-shaped relationship between age and WTP. This study indicates that consumers in Beijing are willing to pay a very high premium for preservative-free food 62% for preservative-free Mooncakes compared to conventional ones.
Keywords: I12; Q18; 330; Preservative-Free Food; Willingness to Pay; Double-Bounded Dichotomous Choice; Mooncakes; Beijing